2015
DOI: 10.1007/s10517-015-3065-8
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective Properties of Indralin in Combination with Monizol in the Treatment of Local Acute and Delayed Radiation Injuries Caused by Local Skin γ-Irradiation

Abstract: Female rats were exposed to local γ-irradiation of the right hindpaw in doses of 30-50 Gy at 131-154 sGy/min dose rate. Radioprotector indralin was administered per os 15 min prior to irradiation, monizol was injected intraperitoneally 5 min after irradiation. Indralin showed marked radioprotective properties both for acute and delayed symptoms of local radiation injuries. In combination with monizol, radioprotective effect of indralin was potentiated to dose reduction factor of 1.4-1.5 both for radiation burn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…[24][25][26][27][28][29][30][31] The radioprotector, indralin (B-190), was also shown to exhibit radioprotective effects on hematopoietic and other tissues, including the intestines, skin, testes, and salivary glands, and it improved survival rates in monkeys after total-body irradiation (TBI) at a dose of 6.8 Gy. [32][33][34][35][36] BIO300, a suspension of synthetic genistein nanoparticles, was developed by the Humanetics Corporation to prevent and mitigate the effects of ARS and DEARE, and radioprotective effects have been demonstrated in mice and NHPs. [37][38][39][40][41][42][43][44] AEOL-10150 is a superoxide dismutase mimetic and metalloporphyrin antioxidant that was shown to be capable of mitigating morbidity and mortality in mice and NHP.…”
Section: The Mechanism Of Ir-induced Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27][28][29][30][31] The radioprotector, indralin (B-190), was also shown to exhibit radioprotective effects on hematopoietic and other tissues, including the intestines, skin, testes, and salivary glands, and it improved survival rates in monkeys after total-body irradiation (TBI) at a dose of 6.8 Gy. [32][33][34][35][36] BIO300, a suspension of synthetic genistein nanoparticles, was developed by the Humanetics Corporation to prevent and mitigate the effects of ARS and DEARE, and radioprotective effects have been demonstrated in mice and NHPs. [37][38][39][40][41][42][43][44] AEOL-10150 is a superoxide dismutase mimetic and metalloporphyrin antioxidant that was shown to be capable of mitigating morbidity and mortality in mice and NHP.…”
Section: The Mechanism Of Ir-induced Injurymentioning
confidence: 99%
“…For example, several studies have shown that γ‐tocotrienol (γGT3), a saturated vitamer of vitamin E, exerts protective effects on hematopoietic stem cells and intestinal crypt cells in the gastrointestinal tract in murine and nonhuman primate (NHP) models, accelerating recovery from IR‐induced injury at various doses (5.8, 6.5, 11, or 12 Gy) 24–31 . The radioprotector, indralin (B‐190), was also shown to exhibit radioprotective effects on hematopoietic and other tissues, including the intestines, skin, testes, and salivary glands, and it improved survival rates in monkeys after total‐body irradiation (TBI) at a dose of 6.8 Gy 32–36 . BIO300, a suspension of synthetic genistein nanoparticles, was developed by the Humanetics Corporation to prevent and mitigate the effects of ARS and DEARE, and radioprotective effects have been demonstrated in mice and NHPs 37–44 .…”
Section: Advancement In the Development Of Radioprotective Agentsmentioning
confidence: 99%